LITERATURE OF REVIEW ANALYSIS OF THE EFFECT OF CASH FLOW VOLATILITY, MARKET CAPITALIZATION AND SALES GROWTH ON COMPANY VALUE: CASE STUDY OF PT. SRI REJEKI ISMAN TBK 2016-2022 - Sofie Aura Rahma (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research is a literature study that examines theinfluence of cash flow volatility, market capitalization,sales growth on company value. This research focuseson the performance of PT PT Sri Rejeki Isman duringthe period 2016 to 2022. This research uses aquantitative design which uses secondary data asinformation in drawing research conclusions. Theanalytical tool used in the form of SPSS will helpresearchers fulfill the model feasibility requirementsand answer the research hypothesis.